Efektivitas Pembelajaran Pendidikan Agama Islam (PAI) terhadap Hasil Belajar Siswa Kelas V SD Sekolah Alam Bogor - Shadam Ali Sagara; Siti Aminah (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2022)
Education is one of the requirements to further improve a better life in the future. Education is also an important factor that determines the development of a nation and state. Learning is a formal activity carried out in schools. In this case the occurrence of an interaction between students, teachers and their environment. The role of a teacher is very important, it will greatly affect student learning outcomes and development. This research was conducted in a formal institution, namely SD Sekolah Alam Bogor, North Bogor area. The purpose of this study is to determine the effectiveness of PAI learning on the learning outcomes of fifth graders at the Bogor Natural Elementary School and to determine the supporting and inhibiting factors of the effectiveness of PAI learning on the learning outcomes of fifth grade students at the Bogor Natural Elementary School. The method used is a qualitative field research (field research) in which data collection is carried out in the field to conduct observations of a phenomenon in a natural state by taking data through interviews, observation and documentation. The results of this study indicate that the effectiveness of PAI learning on the learning outcomes of fifth grade students at Sekolah Alam Bogor has been effective because student learning outcomes have shown above the minimum completeness criteria (KKM). As evidence that the learning process of Islamic religious education is effective, namely the learning process using interesting learning methods and the media used also makes students very enthusiastic when learning takes place. Keyword: learning effectiveness, islamic education, student learning outcomes